2019
DOI: 10.2174/0929866526666190806145740
|View full text |Cite
|
Sign up to set email alerts
|

aeBlue Chromoprotein Color is Temperature Dependent

Abstract: Background: Marine sessile organisms display a color palette that is the result of the expression of fluorescent and non-fluorescent proteins. Fluorescent proteins have uncovered transcriptional regulation, subcellular localization of proteins, and the fate of cells during development. Chromoproteins have received less attention until recent years as bioreporters. Here, we studied the properties of aeBlue, a a 25.91 kDa protein from the anemone Actinia equina. Objective: To assess the properties of aeBlue ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…2d ). On the contrary, aeBlue CRISPRi showed a smaller fold change (2.5-fold), likely due to the suboptimal measurement using absorbance 24 . Yet, visually from parafilm or tube images taken by smartphone, we observed strong pigmentation without CRISPRi and almost no color with CRISPRi ( Fig.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…2d ). On the contrary, aeBlue CRISPRi showed a smaller fold change (2.5-fold), likely due to the suboptimal measurement using absorbance 24 . Yet, visually from parafilm or tube images taken by smartphone, we observed strong pigmentation without CRISPRi and almost no color with CRISPRi ( Fig.…”
Section: Resultsmentioning
confidence: 94%
“…We further linked CRISPRi-based Streptococcus pyogenes dCas9 activity to a pigmentation readout via the control of chromoproteins, which are pigmented proteins that do not require special light wavelengths or filters to visualize. We chose three chromoproteins with visually distinct colors that resemble the RGB color mode (red, yellow/green, and blue): eforRed 20 , fwYellow 21 , and aeBlue 22 . We designed single guide RNAs (sgRNAs) that specifically target the protein-coding sequence of each chromoprotein to achieve efficient and specific transcriptional repression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once diluted by diffusion, the second aspect is the activation of the reporter strain, that canbe evidenced in the surrounding cell death zone and the 'on/off' response can provide information for fast decision making in a similar fashion as described by Zhang et al ( 2013 ) or generate more portable and complementary tools for in-field detection (Roggo and van der Meer 2017 ). The choice of AmilCP is based on a previous study that showed that AmilCP is stable at a wide range of pH values and exposure to urea and an oxidant (Tamayo-Nuñez et al 2020 ), thus making it suitable as a reporter under harsh conditions, such as contaminated water and soil samples (Jiang et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%